Role of Early Enteral Nutrition in Mechanically Ventilated COVID-19 Patients. (18th April 2022) - Haines, Krista; Parker, Virginia; Ohnuma, Tetsu; Krishnamoorthy, Vijay; Raghunathan, Karthik; Sulo, Suela; Kerr, Kirk W.; Besecker, Beth Y.; Cassady, Bridget A.; Wischmeyer, Paul E.
Abstract : OBJECTIVES: Current guidance recommends initiation of early enteral nutrition (early EN) within 24–36 hours of ICU admission in critically ill COVID-19 patients. Despite this recommendation, there is quite limited evidence describing the effect of early EN on outcomes in COVID-19 patients. The association between early EN (within 3 d post intubation) and clinical outcomes in adult COVID-19 patients requiring mechanical ventilation (within 2 d post ICU admission) was evaluated. DESIGN: We performed a nationwide observational cohort study using a nationwide administrative-financial database (Premier) in United States. SETTING: Information pertaining to all COVID-19 patients admitted to ICU from 75 hospitals between April and December 2020 was analyzed. PATIENTS: A total of 861 COVID-19 patients were included. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Clinical outcomes were assessed via regression models to control for patient and hospital characteristics. We identified 513 COVID-19 ICU patients (59.2%) requiring mechanical ventilation who received early EN and had similar baseline characteristics to late EN group. Compared with late EN group, the early EN group had shorter ICU (hazard ratio [HR], 1.39; 95% CI, 1.15–1.68) and hospital length of stays (LOS) (HR, 1.53; 95% CI, 1.23–1.91), fewer mechanical ventilation days (HR, 1.25; 95% CI, 1.01–1.54), and lower cost (–22, 443; 95% CI, –32, 342 to –12, 534). All comparisons were statistically significant ( p < 0.05). CONCLUSIONS: In patients with COVID-19 requiring mechanical ventilation, early EN is associated with earlier liberation from mechanical ventilation, shorter ICU and hospital LOS, and decreased cost. Our results are among the first to support guideline recommendations for initiation of early EN in COVID-19 ICU patients. Further, our data show nearly 40% of critically ill COVID-19 patients fail to have early EN initiated, even at 3 d post initiation of mechanical ventilation. These results emphasize the need for targeted strategies promoting initiation of early EN, as this may lead to improved clinical and economic outcomes in severe COVID-19 patients.